Reading with feeling : affect theory and the Bible - Black, Fiona C.; Koosed, Jennifer L. (Atlanta : SBL Press, 2019)
"The psychological approach known as affect theory focuses on bodily feelings-depression, happiness, disgust, love-and can illuminate both texts and their interpretations. In this collection of essays scholars break new ground in biblical interpretation by deploying a range of affect-theoretical approaches in their interpretations of texts. Contributors direct their attention to the political, social, and cultural formation of emotion and other precognitive forces as a corrective to more traditional historical-critical and linguistic interpretive methods, and response essays push the conversations into profitable directions for future research"--
Cover -- Contents -- Abbreviations -- Introduction -- Affect and Animality in 2 Samuel 12 -- Echoes of How -- The Affective Potential of the Lament Psalms of the Individual -- Public Suffering? -- Prophecy and the Problem of Happiness -- The Disgusting Apostle and a Queer Affect -- "Not Grudgingly, nor under Compulsion" -- "Though We May Seem to Have Failed" -- Responses -- Palpable Traumas, Tactile Texts, and the Powerful Reach of Scripture -- The Rage for Method and the Joy of Anachronism -- Contributors -- Ancient Sources Index -- Modern Authors Index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Critique, interprétation, etc; Bible; Emotions; Emotions; BIBLE; Criticism, interpretation, etc